(untitled) (GEOmedia, 2019)
TNC integrates a Web-app and a cross-platform application whose goal is to support both the on site census of addresses and their validation by responsible users. Each step is carried out according to the ISTAT guidelines, thus realizing standardized and interoperable datasets. The TNC design has followed the rules for the development of enterprise mobile applications.